Optimalisasi Digital Marketing untuk Meningkatkan Brand Awareness pada UMKM IdRink - Alamsyah, Adelya Putri; Jamil, Muhammad; Aris, Valentino (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to analyse the design and optimization of digital marketing to increase the brand awareness of the IdRink MSME through the integration of a website and Instagram. The research employed a Research and Development (R&D) method using the Four-D model (Define, Design, Develop, Disseminate), combined with prototyping techniques and evaluation through blackbox testing. Data were collected through interviews, literature review, observation, Google Analytics, Instagram Insight, and A/B testing questionnaires administered to 100 respondents. The results show that the development of a WordPress-based website and a structured Instagram content plan significantly improved IdRink’s digital performance. Within one month, the audience growth rate increased by 256%, average post reach reached 216%, and website traffic recorded 298 users. Brand awareness measurement indicated brand recognition of 74% and brand recall of 79%, higher than the comparison brand in the local beverage category. These findings indicate that integrating a website and Instagram as a digital marketing strategy is effective in moving IdRink from the unaware-of-brand stage to recognition and recall, expanding market reach, strengthening customer engagement, and building a more professional brand image among young urban consumers. The study recommends maintaining content consistency and utilising digital analytics to support future marketing decision-making.